My first encyclopedia of human body - Sultan, Ahmad (Children publications Karachi, 2012)
My First Encyclopedia of the Human Body is a colorful and accessible guide designed for young learners eager to explore the fascinating world of human anatomy. This book introduces essential concepts in a simple and engaging manner, covering key body parts and systems such as the heart, lungs, muscles, and bones. Each section includes easy-to-understand explanations, fun illustrations, and interactive questions that spark curiosity and encourage discovery. Ideal for early readers, this encyclopedia aims to foster an appreciation for the human body while laying the foundation for future learning in health and science.